2014
DOI: 10.1017/s0266467414000364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate and forest age on plant and caterpillar diversity in the Yucatan, Mexico

Abstract: Abstract:Understanding patterns in plant and herbivorous insect diversity across spatial and temporal scales is fundamental to ecology, but comparative multi-taxonomic studies in tropical seasonally dry forests remain scarce. In 36 sites, distributed over three forest age classes (5–10 y, 10–30 y, >100 y) and three seasonal forest types (dry, intermediate, humid), we sampled plants of different stem diameter classes while caterpillars were sampled across vertically distributed forest layers during three sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…However, insect communities continued to oscillate seasonally, as we also show here. Other research on the Lepidoptera of Mexico also emphasizes the interacting effects of succession and seasonality (Essens et al., 2010). While these processes are infrequently investigated in tandem using long‐term data, complex interactions between the two have also been observed in tropical insect groups outside of Lepidoptera.…”
Section: Discussionmentioning
confidence: 99%
“…However, insect communities continued to oscillate seasonally, as we also show here. Other research on the Lepidoptera of Mexico also emphasizes the interacting effects of succession and seasonality (Essens et al., 2010). While these processes are infrequently investigated in tandem using long‐term data, complex interactions between the two have also been observed in tropical insect groups outside of Lepidoptera.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonality of our sampling period could also explain the low quantity of animal matter in Ocellated Turkey diets. We sampled during the hottest and driest months in Campeche when invertebrate life is reduced (Pozo et al 2008, Essens et al 2014. Ocellated Turkeys hatch between May-July (Steadman et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Annual gross productivity in semi‐evergreen forest of YP is correlated with seasonal variation in evapotranspiration and precipitation, and more leaf material is available at the end of the rainy season (Uuh‐Sonda et al, 2018). Further, univoltine caterpillars are more prone to persist in the rainy to dry season transition (Janzen, 1993; Morais et al, 1999), and seasonality patterns of species abundances have been found for Lepidoptera in this zone of the YP (Essens et al, 2014; Montero‐Muñoz et al, 2013; Pozo et al, 2008). Also, Scherrer et al (2016) showed that in the tropical Cerrado, mean caterpillar diet breadth increased in the dry season when leaves were older.…”
Section: Discussionmentioning
confidence: 99%
“…for Lepidoptera in this zone of the YP (Essens et al, 2014;Montero-Muñoz et al, 2013;Pozo et al, 2008). Also, Scherrer et al (2016) showed that in the tropical Cerrado, mean caterpillar diet breadth increased in the dry season when leaves were older.…”
Section: Interaction Rewiring Highest In Seasonal Than Site-level Metanetworkmentioning
confidence: 97%
See 1 more Smart Citation